Red cell distribution width (RDW) is independently associated with all-cause mortality in adult patients with osteomyelitis admitted to the intensive care unit - Likai Liang; Zhe Chen; Zongyun He; Haibing Tao; Yang Chen; Tao Liu (PLoS ONE, 2025)
Objective This study aims to investigate the correlation between red cell distribution width (RDW) and overall mortality in adults diagnosed with osteomyelitis. Methods In this retrospective study, we examined data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, comprising 2,700 patients with osteomyelitis and available RDW data on the initial day of admission. Employing Kaplan-Meier survival analysis, we assessed the incidence rate of primary outcome events among groups categorized by RDW levels (Q1: RDW ≤ 13.5, Q2: 13.5 < RDW ≤ 14.6, Q3: 14.6 < RDW ≤ 16.1, Q4: 16.1 < RDW), with differences evaluated using the Log-rank test. Subsequently, Cox proportional hazards analyses were conducted to investigate the correlation between RDW and the overall mortality risk. Additionally, we performed stratified analyses based on factors such as gender, congestive heart failure, diabetes, and myocardial infarction to scrutinize the consistency of RDW’s prognostic significance. Results Over the 90-day follow-up, 10.7% of patients with osteomyelitis succumbed. Unadjusted RDW correlated significantly with in-hospital, 30-day, and 90-day mortality (p < 0.05). Higher RDW levels proved more effective in predicting increased risks. RDW emerged as an independent prognostic indicator, showing no significant interactions with sex, congestive heart failure, diabetes, and myocardial infarction (interaction p-values: 0.254 to 0.920). Conclusions The noteworthy link between RDW and heightened all-cause mortality in patients with osteomyelitis who were hospitalized in the intensive care unit highlights RDW’s potential as a valuable marker for identifying at-risk individuals during hospitalization.